SOSIALISASI PRAKTIK CUCI TANGAN PAKAI SABUN (CTPS) SERTA PEMANFAATAN LIMBAH UNTUK SARANA CUCI TANGAN SEBAGAI UPAYA MENJAGA KESEHATAN DIRI DAN LINGKUNGAN - Legis Ocktaviana Saputri; Arina Windri Rivarti; Mahacita Andanalusia; Lalu Auliya Akraboe Littaqwa; M. Said Ramdlan (Jurnal Abdi Insani, 2023)
Maintaining personal and environmental health can be implemented through Clean and Healthy Behavior (PHBS). One form of application is washing hands with soap (CTPS). CTPS has proven to be effective in preventing disease transmission from one individual to another. CTPS practice is an absolute necessity, while the availability of CTPS facilities is still inadequate. This activity aims to increase the knowledge of elementary and junior high school students and teachers at Pondok Pesantren Nurul Ijtihad Al-Ma'arif NU Central Lombok about CTPS as a strategy to minimize the spread of disease (Covid-19) in the school environment. This activity is carried out in the form of socialization. CTPS Practice Education refers to the procedure for washing hands properly and correctly according to the World Health Organization (WHO). Participants were also introduced to the use of solid waste as an ideal CTPS facility and how to manage the remaining CTPS liquid waste. Pre-test and post-test were given to test the success of the activities carried out. This activity was attended by 75 participants consisting of students, teachers and regular recitation participants at the Nurul Ijtihad Al-Ma'arif NU Islamic Boarding School in Central Lombok. Participants were given education by 3 (three) experts regarding good and correct CTPS practices, the use of solid waste for making CTPS facilities, and the management of liquid waste left over from CTPS practices so as not to have a negative impact on the environment. This activity ran smoothly and proved successful in increasing participants' understanding as indicated by the pre-test and post-test scores which increased from 50.5% to 61.97%. The ideal CTPS practice needs to be constantly reminded in order to prevent disease transmission. Utilization and management of waste in the practice of CTPS is a strategy to prevent environmental pollution.